The Meaning Of Progress According To Shaykh Abdullah Fahim - Badri, Khairul Nizam Bin Zainal (Islamadina : Jurnal Pemikiran Islam, 2023)
The Malays began to gain awareness of nationalism in the early 20th century AD. The figures among Kaum Muda (Reformist Movement) are considered a precursor to the consciousness movement. Kaum Muda who are heavily influenced by the thinking of the Egyptian reformist figure, Shaykh Muhammad Abduh, aspired to expand modern thinking so that Muslims can stand as high as other races and take over the reins of government from the British colonialists. But the attitude of Kaum Muda likes to criticize Malay Sultans, and generate debate with scholars of the Kaum Tua (Traditionalist) not much progress can be achieved. At the same time, Shyakh Abdullah Fahim, one of the scholars of the Kaum Tua also had the same thought as Kaum Muda, which encourages people to develop themselves and Malays have the awareness to govern the country. This study seeks to examine the thinking of Shaykh Abdullah Fahim from his point of view on development and religion and its impact on progress. The method used in the study is qualitative based. The approach used to obtain information is by applying archival research. The results of the study found that Shaykh Abdullah Fahim still adheres to the basic principles of the Kaum Tua, namely Ahl Al-Sunnah Wa Al-Jamaah in an effort to develop the nation and country. The three things that Shaykh Abdullah Fahim emphasized to achieve progress were the establishment of educational institutions, involvement in the production of writing materials to inspire awareness, and the development of the youth generation